2019
DOI: 10.1097/jsm.0000000000000742
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Knee Osteoarthritis in Retired Professional Footballers: A Cross-Sectional Study

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
20
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 43 publications
8
20
2
Order By: Relevance
“…Parekh et al showed 59±11.7 years mean age and another one showed 38±5 years. 21 We found 46.55% prevalence of KOA among the footballers. The prevalence of KOA were 50%, 49%, 80% and 27.5% in previous four studies.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Parekh et al showed 59±11.7 years mean age and another one showed 38±5 years. 21 We found 46.55% prevalence of KOA among the footballers. The prevalence of KOA were 50%, 49%, 80% and 27.5% in previous four studies.…”
Section: Discussionmentioning
confidence: 58%
“…Parekh et al 21 showed knee injury, age, gout and career training to be significant. Gouttebarge, et al 9 showed knee injury was significant risk factor for developing KOA.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, OA was self-reported and likely to introduce a bias. However, the questionnaire has been widely used in studies to assess selfreported OA (Kojima et al 2017;Hackney et al 2019;Parekh et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A majority of these studies have reached a consensus that the concerned factors are positively related to OA. Among them, There are six studies indicating that gout is likely to have a positive association with OA, [ 23 26 ] or increase the risk of KR, HR, and TJR, [ 3 , 27 ] and one of these studies also pointed out that ULT did not reduce the involved risks. [ 3 ] As for HU, four studies suggested a positive association with OA.…”
Section: Discussionmentioning
confidence: 99%